Avaliação das políticas públicas de resíduos sólidos à luz do desenvolvimento sustentável: estudo de municípios da região sudoeste do Paraná - Ludwig, Caroline (2021)
In Brazil, the management of Urban Solid Waste - USW is a responsibility of the municipalities, which aim, through their laws and the elaboration of the Municipal Plan for Integrated Solid Waste Management - PMGIRS, to promote the integrated management of solid waste, combining environmental, economic and social aspects to public policies. The aim of this research is to evaluate public policies related to municipal solid waste management in the southwest region of Paraná in the light of sustainable development. In this sense, the analysis of the PMGIRS, master plans and Multi-Year Plans - PPAs for the 2018-2021 quadrennium of the municipalities of Francisco Beltrão, Pato Branco, Dois Vizinhos and Coronel Vivida was carried out to verify the alignment of these documents with the National Solid Waste Policy - PNRS and Sustainable Development. The evaluation of the PMGIRS took place through the analysis of compliance of its content with the 19 items present in Article 19 of Law 12.305/2010. The analysis of the master plans was carried out with the help of the Nvivo version 2012 software, in which references were coded from an environmental, economic, institutional and social perspective relevant to the integrated management of solid waste. The PPAs were analyzed according to the environmental, economic, spatial, institutional, social and cultural dimensions of sustainable development. The research is methodologically supported by bibliographic and documentary analysis of secondary data, mainly from PMGIRS, Master Plans and Municipal Multi-year Plans. The research was developed in three phases: the first exploratory phase, the second descriptive and finally, the third analytical phase. The results showed that in all municipalities the items that addressed selective collection, the correct disposal of solid waste and the performance of cooperatives and recycling associations were met. The items that address the inspection, monitoring and renewal of the PMGIRS were the items least attended to. In the master plans, references were found that can contribute to the implementation of integrated solid waste management along with urban planning, mainly from an environmental perspective. In all PPAs, there were budget programs focused on solid waste management, which is within the environmental dimension. The identification of the relationship between the PMGIRS, master plans and PPAs pointed out that there is a lack of balance between the environmental, economic, institutional and social dimensions present in each policy analyzed, making sustainable development from the integrated management of solid waste difficult.